Molecular fluorescence endoscopy targeting vascular endothelial growth factor a for improved colorectal polyp detection - Tjalma, Jolien J.; Garcia-Allende, P. Beatriz; Hartmans, Elmire; Van Scheltinga, Anton G. Terwisscha; Boersma-Van Ek, Wytske; Glatz, Juergen; Koch, Maximilian; Van Herwaarden, Yasmijn J.; Bisseling, Tanya M.; Nagtegaal, Iris D.; Timmer-Bosscha, Hetty; Koornstra, Jan Jacob; et al. (Journal of Nuclear Medicine, 2016)
Small and flat adenomas are known to carry a high miss-rate during standard white-light endoscopy. Increased detection rate may be achieved by molecular fluorescence endoscopy with targeted nearinfrared (NIR) fluorescent tracers. The aim of this study was to validate vascular endothelial growth factor A (VEGF-A) and epidermal growth factor receptor (EGFR)-targeted fluorescent tracers during ex vivo colonoscopy with an NIR endoscopy platform. Methods: VEGF-A and EGFR expression was determined by immunohistochemistry on a large subset of human colorectal tissue samples-48 sessile serrated adenomas/polyps, 70 sporadic high-grade dysplastic adenomas, and 19 hyperplastic polyps-and tissue derived from patients with Lynch syndrome-78 low-grade dysplastic adenomas, 57 high-grade dysplastic adenomas, and 31 colon cancer samples. To perform an ex vivo colonoscopy procedure, 14 mice with small intraperitoneal EGFR-positive HCT116luc tumors received intravenous bevacizumab-800CW (anti-VEGF-A), cetuximab-800CW (anti-EGFR), control tracer IgG-800CW, or sodium chloride. Three days later, 8 resected HCT116luc tumors (2-5 mm) were stitched into 1 freshly resected human colon specimen and followed by an ex vivo molecular fluorescence colonoscopy procedure. Results: Immunohistochemistry showed high VEGF-A expression in 79%-96% and high EGFR expression in 51%-69% of the colorectal lesions. Both targets were significantly overexpressed in the colorectal lesions, compared with the adjacent normal colon crypts. During ex vivo molecular fluorescence endoscopy, all tumors could clearly be delineated for both bevacizumab-800CW and cetuximab-800CW tracers. Specific tumor uptake was confirmed with fluorescent microscopy showing, respectively, stromal and cell membrane fluorescence. Conclusion: VEGF-A is a promising target for molecular fluorescence endoscopy because it showed a high protein expression, especially in sessile serrated adenomas/polyps and Lynch syndrome. We demonstrated the feasibility to visualize small tumors in real time during colonoscopy using a NIR fluorescence endoscopy platform, providing the endoscopist a wide-field redflag technique for adenoma detection. Clinical studies are currently being performed in order to provide in-human evaluation of our approach.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Endoscopy; Molecular imaging; Near-infrared fluorescence; Optical imaging; Vascular endothelial growth factor A